The Effectiveness of Blinking Therapy in Dry Eye Disease: An Evidence-Based Case Report - Fredy Christianto; Nuri Purwito Adi (ILUNI MKK FKUI and PRODI MKK FKUI, 2022)
Background: Dry eye disease (DED) is a group of tear film disturbances that are caused by a decrease in tear production or tear film instability. One of the causes of DED is reduced tear secretion, which often happens in visual display terminal (VDT) workers. Blinking therapy is one of the therapies that can be given to DED workers to increase blink rate and reduce the number of incomplete blinks. Methods: Literature searching was done on database such as Pubmed, Cochrane Library, and Google Scholar. The keywords used in the literature search were dry eye disease, blinking therapy, and ocular surface disease index. Three articles were chosen and critically appraised. Results: Blinking therapy can be done using conventional methods, using animation software on a computer, or by using specifically designed wink glass. Blinking therapy showed statistically significant changes in OSDI scores, with therapy duration ranging from 20 minutes to 4 weeks. Conclusion: Blinking therapy can be done as a treatment for DED workers to improve dry eye symptoms as measured in OSDI.